Islam at Jesuit Colleges and Universities - Aysha Hidayatullah (Smashwords Edition, 2016)
On April 10-11, 2015 the University of San Francisco hosted the national conference, "Islam at U.S. Jesuit Colleges and Universities." The overall aim of the conference was to examine the evolution of the mission, objectives, and identity of Catholic Jesuit colleges and universities in light of the expansion of the study of Islam and the growing presence of Muslim faculty, staff, and students on our campuses.